The evolution of annuality in association with a shift to more arid environments in the daisy genera Ifloga and Tricogyne - Trisos, Christopher (Department of Biological Sciences, 2017)
An annual life history is often viewed as a model adaptation to arid environments. Annuality is predicted to have evolved in response to low adult survival and high seedling survival. In this study I evaluated the idea that increases in aridity should be associated with the evolution of an annual life history. I also investigated the correlated evolution of annuality and growth form. Ancestral character states for life history characters and climate variables were mapped onto a molecular phylogeny (obtained using plastid trnL-trnF and psbA-trnH and nuclear ETS sequences) of the genera Trichogyne and Ifloga (Asteraceae). Bayesian methods were used for phylogeny inference and maximum likelihood methods for ancestral state reconstructions. Only two phylogenetically independent contrasts were obtained and so the association between changes from annuality to perenniality and increases in aridity along branches of the tree were recorded and evaluated using Fisher's exact test. In order to account for ancestral character state reconstruction uncertainty, four different possible scenarios suggested by the maximum likelihood methods for the evolution of annuality were examined. This is the first molecular phylogeny of the group. Bayesian analysis of the sequence data places the Trichogyne+ Ifloga clade within the Gnaphileae. The genus Ifloga is shown to be paraphyletic. Trichogyne ambigua, as currently described, is polyphyletic and may contain two species. The origin of the Trichogyne+ Ifloga clade is within southern Africa and a northwards migration via the arid corridor is suggested to explain the disjunct distribution of the two Northern Hemisphere species. There is an association between the duration of the moisture growing season and the evolution of annuality. This is consistent with the idea that annuality is favoured by long drought periods making perennation difficult. The evolution of annuality was correlated with a non-woody, tufted, growth form. Amphi-basicarpy was discovered for T. polycnemoides, making it only the second known example of this reproductive strategy within Asteraceae.